2023
DOI: 10.1002/advs.202301868
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Human Endometrial Assembloids with a Luminal Epithelium using Air–Liquid Interface Culture Methods

Jiwen Tian,
Jie Yang,
Tingwei Chen
et al.

Abstract: The endometrial lining of the uterus is essential for women's reproductive health and consists of several different types of epithelial and stromal cells. Although models such as gland‐like structures (GLSs) and endometrial assembloids (EnAos) are successfully established, they lack an intact luminal epithelium, which makes it difficult to recapitulate endometrial receptivity. Here, a novel EnAo model (ALI‐EnAo) is developed by combining endometrial epithelial cells (EnECs) and stromal cells (EnSCs) and using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 83 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…Single-cell sequencing of full-thickness normal human endometrium uterine from proliferative and secretory phases revealed four populations of stromal cells, secretory stroma (SCGB1D2), SFRP4 + stroma (SFRP4), DCN + stroma (DCN) and inflammatory stroma (IL6) [ 30 ]. In our reported human endometrial assembloids with a luminal epithelium, EnSCs were identified into six endometrial stromal cells populations, of which the EnSC subpopulation 2 (EsS2) is positive of CXCL8, CXCL1 and IL6 genes and exhibits immunoregulatory properties [ 53 ]. These studies suggest that immunoregulation of stromal cells may be exerted by some specific stromal cell subpopulations, and different stromal cell subpopulations are likely to play different roles in endometrial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell sequencing of full-thickness normal human endometrium uterine from proliferative and secretory phases revealed four populations of stromal cells, secretory stroma (SCGB1D2), SFRP4 + stroma (SFRP4), DCN + stroma (DCN) and inflammatory stroma (IL6) [ 30 ]. In our reported human endometrial assembloids with a luminal epithelium, EnSCs were identified into six endometrial stromal cells populations, of which the EnSC subpopulation 2 (EsS2) is positive of CXCL8, CXCL1 and IL6 genes and exhibits immunoregulatory properties [ 53 ]. These studies suggest that immunoregulation of stromal cells may be exerted by some specific stromal cell subpopulations, and different stromal cell subpopulations are likely to play different roles in endometrial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although models such as gland-like structures and endometrial assembloids have been successfully established, 114,115 the lack of intact luminal epithelium makes it difficult to recapitulate endometrial receptivity. Using an improved matrix and air-liquid interface culture method, Tian et al 116 developed a novel ALI-EnAo model composed of endometrial epithelial cells and stromal cells. ALI-EnAos recapitulated endometrial anatomy, cell composition, gene expression profiles, and hormone-induced menstrual cycle changes in vitro.…”
Section: Recent Research Progress In Organoids and 3d Embryo Culturementioning
confidence: 99%
“…In recent years, efforts have been made to develop platforms aimed at rebuilding or simulating the endometrial tissue, including two-dimensional (2D) cell culture systems and explant models to illustrate the histological and molecular characteristics of the endometrium [ [6] , [7] , [8] ]. Additionally, developing more dynamic and adjustable methods based on bioengineering technologies by taking advantage of replicating tissue structures and functions is essential to narrowing physiological gaps between tissues or organs in vivo and culture models in vitro [ 9 ].…”
Section: Introductionmentioning
confidence: 99%